2016
DOI: 10.1111/dmcn.13084
|View full text |Cite
|
Sign up to set email alerts
|

Auditory neuropathy in Brown–Vialetto–Van Laere syndrome due to riboflavin transporter RFVT2 deficiency

Abstract: ABBREVIATIONS ABR Auditory brainstem reflexes ANSD Auditory neuropathy spectrum disorder BVVL Brown-Vialetto-Van Laere syndrome OAE Otoacoustic emissions AIM Mutations in the genes encoding the riboflavin transporters RFVT2 and RFVT3 have been identified in Brown-Vialetto-Van Laere syndrome, a neurodegenerative disorder characterized by hearing loss and pontobulbar palsy. Treatment with riboflavin has been shown to benefit individuals with the phenotype of RFVT2 deficiency. Understanding the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(111 reference statements)
2
17
0
1
Order By: Relevance
“…Clinically, the patient demonstrated a remarkable improvement in sensory ataxia followed by improvement in bulbar function. Sensorineural deafness did not improve, which is in keeping with the pattern noted in the literature . The differential diagnosis of abnormal dorsal column signals and sensory ataxia includes deficiencies of vitamin B 12 , folate, copper, and vitamin E, as well as human immunodeficiency virus, tabes dorsalis, and demyelination.…”
Section: Discussionsupporting
confidence: 88%
“…Clinically, the patient demonstrated a remarkable improvement in sensory ataxia followed by improvement in bulbar function. Sensorineural deafness did not improve, which is in keeping with the pattern noted in the literature . The differential diagnosis of abnormal dorsal column signals and sensory ataxia includes deficiencies of vitamin B 12 , folate, copper, and vitamin E, as well as human immunodeficiency virus, tabes dorsalis, and demyelination.…”
Section: Discussionsupporting
confidence: 88%
“…There have since been a further 10 publications reporting on 23 newly diagnosed RTD2 cases, and 12 reporting on 27 newly diagnosed RTD3 cases . A patient harboring a heterozygous pathogenic mutation in SLC52A3 and heterozygous SLC52A2 variant of unknown significance has been described, which will be considered as a RTD3 case here.…”
Section: Riboflavin Transporter Deficienciesmentioning
confidence: 99%
“…Previous studies that aimed to understand the characteristics of hearing loss in patients with riboflavin transporter deficiency type 2 identified that hearing loss was due to auditory neuropathy. 30,31 Auditory neuropathy is a rare condition reported in only 8% of children per year who are newly diagnosed with hearing loss. 32 Otoacoustic emissions testing used in most American states as part of their universal hearing screening program will not identify auditory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that a cochlear implant can have positive effects on both sound and speech perception in children with riboflavin transporter deficiency. 30,31 It has been reported that children with auditory neuropathy receive greater benefit if they are implanted early before a substantial delay in their language development. 33 In our cohort, we found a potential significant delay in the recognition of auditory neuropathy and for receiving a cochlear implant, which may have resulted in a poorer hearing outcome post-implant.…”
Section: Discussionmentioning
confidence: 99%